Derdegolfbestuur: ’n prinsipiële besinning - Kruger, S. (Koers, 1997)
Third Wave management: A deliberation on the principlesThe postmodern understanding of reality revolves around the idea that there are no absolute values - everything is in flux. Postmodernism is a revolutionary epoch in man's existence and implies a transitionary state from modernism to a new era of thinking. The science of management, being dynamic, is continually interpreting the status of presentday companies. Toffler proposed a managerial theory called Third Wave management. This theory embodies the current postmodern understanding of reality. While a superficial similarity exists between Third Wave management and the New Age Movement, it does not necessarily mean that Third Wave management shares the ideological and spiritual presuppositions of the New Age Movement. Third Wave management theory can be interpreted as part of a post-modernist paradigm which eventually precipitates in middle range management science (a mesoparadigm). Several managerial models and structures can thus be developed.